Profiling of miRNAs in Mouse Peritoneal Macrophages Responding to Echinococcus multilocularis Infection - Guo, Xiaola; Zheng, Yadong (Frontiers in Cellular and Infection Microbiology, 2020)
Alveolar echinococcosis (AE) is a zoonotic helminthic disease caused by infection with the larval of Echinococcus multilocularis in human and animals. Here, we compared miRNA profiles of the peritoneal macrophages of E. multilocularis-infected and un-infected female BALB/c mice using high-throughput sequencing. A total of 87 known miRNAs were differentially expressed (fold change ≥ 2, p-value < 0.05) in peritoneal macrophages in mice 30- and 90-day post infection compared with ones in un-infected mice. An increase of mmu-miR-155-5p expression was observed in peritoneal macrophages in E. multilocularis-infected mice. Compared with the control group, the production of nitric oxide (NO) was increased in peritoneal macrophages transfected with mmu-miR-155-5p mimics at 12h after transfection (p < 0.001). Two key genes (CD14 and NF-κB) in the LPS/TLR4 signaling pathway were also markedly altered in mmu-miR-155-5p mimics transfected cells (p < 0.05). Moreover, mmu-miR-155-5p mimics suppressed IL6 mRNA expression and promoted IL12a and IL12b mRNA expression. Luciferase assays showed that mmu-miR-155-5p was able to bind to the 3' UTR of the IKBKE gene and decreased luciferase activity. Finally, we found the expression of IKBKE was significantly downregulated in both macrophages transfected with mmu-miR-155-5p and macrophages isolated from E. multilocularis-infected mice. These results demonstrate an immunoregulatory effect of mmu-miR-155 on macrophages, suggesting a role in regulation of host immune responses against E. multilocularis infection.